Penggunaan Media Audio-Visual dalam Pembelajaran Kelas sebagai Faktor yang Mempengaruhi Pemahaman Konsep Siswa Sekolah Dasar - Faridatus Shofa; Didit Darmawan; Rahayu Mardikaningsih (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Educational developments in the 21st century demand an increase in students’ critical thinking skills and conceptual understanding, particularly at the elementary school level, where students still struggle to grasp abstract concepts through conventional teaching methods. This study aims to analyze the impact of audiovisual media on elementary students’ conceptual understanding and to identify the factors influencing it. The method used is a Systematic Literature Review (SLR) with a qualitative approach applied to 10 relevant research articles published between 2020 and 2025. The analysis was conducted through the stages of identification, selection based on inclusion criteria, evaluation, and thematic synthesis. The results indicate that audiovisual media consistently have a positive impact on students’ conceptual understanding because they can present abstract material in a more concrete and easily understandable manner. Additionally, audiovisual media also contribute to enhancing students’ motivation and engagement in the learning process. However, their effectiveness remains influenced by instructional design, the purpose of media use, and students’ individual circumstances. In conclusion, audiovisual media are an effective instructional strategy for improving elementary school students’ conceptual understanding and should be appropriately integrated into the learning process to support improvements in educational quality.